Dose-response relationships between physical activity and exercise health beliefs, meaning in life, and psychological richness among college students: a restricted cubic spline analysis - Zongyu Liu; Bochuan Zhao; Haitao Niu (BMC Public Health, 2026)
Abstract Background Physical activity has been associated with multiple psychological outcomes, but most previous studies have assumed linear relationships, leaving its potentially nonlinear dose-response associations with cognitive, existential, and experiential outcomes among undergraduate students insufficiently understood. This study examined the dose-response relationships between physical activity and exercise health beliefs, meaning in life, and psychological richness among undergraduate students, and tested the moderating roles of academic year and gender. Methods A cross-sectional survey was conducted with 673 undergraduate students, measuring their physical activity levels, exercise health beliefs, meaning in life, and psychological richness. Restricted cubic spline (RCS) models were employed to fit dose-response curves between physical activity and the three dependent variables, and interaction terms were used to test the moderating effects of demographic variables. Results Significant dose-response associations were observed between physical activity and exercise health beliefs ( F = 52.12, p < 0.001), meaning in life ( F = 11.36, p < 0.001), and psychological richness ( F = 13.59, p < 0.001). The association between physical activity and exercise health beliefs departed significantly from linearity (nonlinearity test F = 26.54, p < 0.001), displaying a curvilinear pattern with diminishing increments. Academic year significantly moderated the associations of physical activity with psychological richness ( F = 2.56, p = 0.007) and meaning in life ( F = 1.91, p = 0.047), indicating that the overall fitted associations varied across the four academic-year groups. Conclusions The association between physical activity and exercise health beliefs exhibited a significant nonlinear dose-response pattern, whereas academic year moderated the associations of physical activity with meaning in life and psychological richness. These cross-sectional findings may inform the design and evaluation of university physical activity programs that consider nonlinear association patterns and variation across academic years.